Factors influencing the utilization of biological medicines in the Free State (South Africa) - Mocke-Richter, M. (University of the Free State, 2019)
English: Biological Medicines are substances derived from animal or other biological origin, and are used to treat, diagnose or prevent mainly inflammatory diseases and cancer. The use thereof has grown worldwide and is aimed at improving the quality of life of patients. However, in South Africa access to Biological Medicines remains limited. Unfortunately, the use of Biological Medicines has presented challenges with regard to the requirements for appropriate therapeutic responses and their side-effects. In order to obtain an appropriate therapeutic response, appropriate patients have to be selected and continuously monitored during therapy. The two-fold aim of the study was to identify the factors influencing the utilization of Biological Medicines in the Free State (South Africa), and to develop a framework for the use of Biological Medicines in South Africa. Therefore the objective of the study was to determine perception, knowledge of and training in Biological Medicines by clinicians who have been practising for two years or less since graduating and to identify the factors that might influence the prescribing of Biological Medicines by some doctors in the Free State. It was also important to evaluate patient knowledge and experience with Biological Medicines and identify the factors (age, gender, race, disease, patient perception, and adverse effects) that might influence patient compliance with Biological Medicines in some institutions in South Africa. The abovementioned helped to develop a framework for the use of Biological Medicines in South Africa. A cross sectional study design was used. The literature review was used as the foundation to compile the questionnaires. The study consists of three different questionnaires, one for the newly qualified doctors; one for the specialists who prescribed Biological Medicines as well as the one for the patients who used Biological Medicines. The Delphi survey consisted of the data generated through the previous phases of the study, which consisted of literature cited, as well as three different questionnaires. For the purpose of this study, the Delphi method was used as a tool for achieving consensus, where experts validated some of the aspects and criteria with the view to draft a framework. As it was, out of the 79 newly qualified doctors in the Mangaung district (Bloemfontein) in the Free State, 79,7% (n = 63) completed the questionnaire. There were 17 specialists that prescribed Biological Medicines in the Free State, and 70,6% (n = 12) of them completed the questionnaire. Biological Medicines do not have more adverse effects than pharmaceutical agents. As it was, out of the 38 patients that used Biological Medicines and were identified by the clinicians, 81,6% completed the questionnaire. In the Delphi questionnaire study, there were 15 panel members that responded out of 20 who received the invitation. In conclusion, there was a general lack of knowledge on Biological Medicines among newly qualified doctors; therefore, there was a need to educate these young doctors about Biological Medicines, and to offer support in the form of a framework on the use of Biological Medicines to ensure that current patients benefit. The clinicians have limited knowledge of the pharmacology of Biological Medicines and therefore there is still much to be learned about the adverse effects of Biological Medicines. Furthermore, there is a need to educate the prescribers, and to offer support in the form of a framework on the use of Biological Medicines to ensure that current patients benefit and also to improve the procurement process to obtain Biological Medicines. It was established that Biological Medicines are improving the quality of life of patients. Seen from above, Biological Medicines have so far had a positive impact on patient lives; therefore, there was a need expressed to make Biological Medicines more available to patients who need it. The framework containing the findings of the research will be brought to the attention of the Biological Medicine Committee of South Africa, the Medicine Control Council, as well as the National Department of Health. It will furthermore be recommended that the framework that was developed may be adapted by the health care professionals who prescribe Biological Medicines. The research findings were submitted to academic journals with a view to publication, as well as presented at conferences.

Afrikaans: Biologiese Medisyne is middels wat van diere of ander biologiese oorsprong is, en word gebruik om hoofsaaklik inflammatoriese siektes en kanker te behandel, diagnoseer of te voorkom. Die gebruik daarvan het wêreldwyd toegeneem met die doel om die lewenskwaliteit van pasiënte te verbeter. In Suid-Afrika is toegang tot hierdie middels beperk. Ongelukkig het die gebruik van Biologiese Medisyne tot dusver uitdagings gebied met betrekking tot die vereistes vir geskikte terapeutiese response en hul newe-effekte. Ten einde geskikte terapeutiese response te bekom, word geskikte pasiënte geselekteer, en deurlopend gemonitor gedurende terapie. Die tweevoudige oogmerk van die studie was om die faktore wat die gebruik van Biologiese Medisyne in die Vrystaat provinsie van Suid-Afrika beïnvloed, te identifiseer en om ‘n raamwerk daar te stel vir die gebruik van Biologiese Medisyne in Suid-Afrika. Derhalwe was die doelwit van die studie om Vrystaatse dokters wat die afgelope twee jaar gegradueer het, se persepsie, kennis en opleiding aangaande Biologiese Medisyne te bepaal, sowel as om die faktore wat die dokters moontlik kan beïnvloed in die voorskryf van Biologiese Medisyne, te identifiseer. Dit was ook noodsaaklik om pasiënte se kennis en ervaring van Biologiese Medisyne te identifiseer sowel as die faktore (ouderdom, geslag, ras, siekte, pasiëntpersepsie en nadelige gevolge) te identifiseer ten opsigte van pasiënt-inwilliging om Biologiese Medisyne in sommige instellings in Suid-Afrika te gebruik. ʼn Kruisdeursnee studie-ontwerp is in hierdie studie gebruik. Die literatuuroorsig is gebruik as die fondasie om die vraelyste op te stel. Die studie bestaan uit drie verskillende vraelyste: een vir die nuut gekwalifiseerde dokters, een vir die spesialiste wat Biologiese Medisyne voorskryf sowel as een vir die pasiënte wat Biologiese Medisyne gebruik. Die Delphi-metode het bestaan uit die data wat ingesamel is deur die vorige fases van die studie, wat bestaan het uit die literatuuroorsig sowel as die drie vraelyste. Vir die doeleindes van hierdie studie is die Delphi-metode gebruik as ‘n instrument om konsensus te bereik, waar kundiges sommige van die aspekte en kriteria valideer met die oog om ‘n raamwerk daar te stel. Vanuit die 79 nuut gekwalifiseerde dokters in die Mangaung-distrik (Bloemfontein) in die Vrystaat, het 79,7% (n = 63) die vraelyste voltooi. Daar was 17 spesialiste wat Biologiese Medisyne in die Vrystaat voorskryf, en 70,6% (n = 12) van die spesialiste het die vraelys voltooi. Biologiese Medisyne het nie meer newe-effekte as farmaseutiese middels nie. ʼn Totaal van 81,6% van die 38 pasiënte wat Biologiese Medisyne gebruik het en deur die spesialiste uitgewys is, het die vraelys voltooi. Die Delphi-vraelys is deur 15 van die uitgenooide 20 paneellede voltooi. Laastens was daar ‘n gebrek aan kennis oor Biologiese Medisyne onder nuutaangestelde dokters en was dit nodig om hierdie jong dokters onderrig te gee in die gebruik van Biologiese Medisyne en om ondersteuning te bied in die vorm van ‘n raamwerk vir die gebruik van Biologiese Medisyne en derhalwe huidige pasiënte te bevoordeel. Dokters het nog heelwat onkundigheid ten opsigte van Biologiese Medisyne en derhalwe te leer van die newe-effekte van hierdie soort medisyne. Voorts is dit belangrik dat dokters meer te wete kom van die farmakologiese eienskappe van Biologiese Medisyne. Selfs verskaffers van Biologiese Medisyne moet opleiding ontvang en moet die raamwerk ontvang om hulle by te staan om huidige pasiënte te bevoordeel sowel as om verkrygingsprosesse te leer. Biologiese Medisyne het ‘n positiewe impak op pasiënte se lewens. Gesien in hierdie lig, was daar ‘n behoefte om Biologiese Medisyne meer toeganklik vir pasiënte te maak wat dit nodig het. Die raamwerk bestaan uit die bevindinge van die navorsing en sal beskikbaar gestel word aan die Biologiese Medisynekomitee van Suid-Afrika. Ook die Medisynebeheerraad en die Departement van Gesondheid sal dit ontvang. Daar word voorts aanbeveel dat die raamwerk aangepas mag word vir professionele gesondheidswerkers wat Biologiese Medisyne voorskryf. Die navorsingsresultate is aan akademiese joernale gestuur met die oog op publikasie, of om as referate by konferensies te dien.
Keywords: Thesis (Ph.D. (Pharmacology))--University of the Free State, 2019; Biological medicines; Monoclonal antibodies; Delphi method; Factors influencing the use of biological medicines; Framework for use of biological medicines